Effects of different cooking methods and of the inclusion of chestnut (Castanea sativa Miller) in the finishing diet of Celta pig breed on the physicochemical parameters and volatile profile of Longissimus thoracis et lumborum muscle. (November 2020) - Echegaray, Noemí; Paterio, Mirian; Domínguez, Rubén; Purriños, Laura; Bermúdez, Roberto; Carballo, Javier; Lorenzo, José M.
Graphical abstract: Highlights: The inclusion of chestnut in the finishing diet of Celta pig breed was assessed. Four culinary treatments were used: roasting, grilling, frying and microwaving. The shear force of pig meat was not affected by the heat treatment. Steaks from microwaved and fried treatments presented the highest cooking losses. Grilling and microwaving treatment showed more negative effects on the lipid oxidation. Abstract: The effect of different cooking methods and the influence of the use of chestnuts ( Castanea sativa Miller) rather than commercial feed in the pig diet on physicochemical characteristics, oxidative stability and volatile profile of cooked Longissimus thoracis et lumborum Celta pig muscle was investigated. Four treatments were used for cooking meat from both diets: roasting, grilling, frying and microwaving. Analysis of cooked meat included the proximate composition (moisture, protein, fat, and ash contents), colour parameters (L*, a*, b*), cooking loss, shear force, lipid oxidation and volatile compounds. Overall, the cooking technique significantly affected the proximal composition, colour parameters, cooking loss, TBARS and volatile profile of Longissimus thoracis et lumborum, whereas the shear force was not affected by the heat treatment. Frying was the technique that led to a greater presence of fat. Additionally, microwaved and fried samples presented the highest cooking losses. Regarding to the lipid oxidation, grilling and microwaving showed more negative effects on the samples, while frying involved a lower presence of TBARS and hexanal contents. The major volatile compounds were aldehydes for all cooking methods except for the frying technique, which besides presented the lowest amount of total volatiles compounds. With respect to the finishing diet, in general the use of chestnuts did not affect the chemical composition, colour parameters, cooking loss and shear force of cooked Longissimus thoracis et lumborum . Nevertheless, a significant decrease in the TBARS value was found with the inclusion of this fruit in the finishing diet. At the same time, the use of chestnuts also affects the content of some volatile compounds such as heptanal and furan, 2-pentyl.